G557 Value of scintigraphy in identifying cause of congenital hypothyroidism. (May 2019) - Worth, C; Hird, B; Tetlow, L; Wright, N; Patel, L; Banerjee, I
Abstract : Background: Identification of Congenital Hypothyroidism (CHT) with Blood Spot (BS) Thyroid Stimulating Hormone (TSH) is an essential part of Newborn Screening (NBS) in the UK. A screen positive result requires confirmation with plasma free thyroxine (fT4) and TSH. Technetium-99m scintigraphy can be used to define size and location of the thyroid. We investigated the utility of scintigraphy to identify the cause of CHT and impact on clinical management. Methods: Newborns who were screen positive for CHT (initial screening BS TSH >20 mU/L or >8 mU/L on initial sample confirmed in the second sample taken 7–10 days later) at an NBS centre between 2007 and 2017 had scintigraphy at diagnostic assessment. Scintigraphy data [normal/large gland (dyshormonogenesis), small/absent (dysplasia) and abnormal position (ectopia)] was tested for correlation with BS TSH, plasma TSH and fT4. Results: 418 newborns were referred from 5 34 783 newborns screened by NBS. 303 had confirmed CHT and underwent scintigraphy. The largest group was dyshormonogenesis (n=139, 45.7%) followed by ectopia (n=84, 27.6%) and dysplasia (n=80, 26.3%). Median BS TSH (mU/L) was lower in dyshormonogenesis than in ectopia and dysplasia [23.0 vs 106.0 vs 172.0][p<0.001]. Plasma TSH showed similar differences. fT4 levels (pmol/L) were higher in dyshormonogenesis than in ectopia and dysplasia [12.1 vs 9.6 vs 4.0][p<0.001]. Initial levothyroxine doses (micrograms/day) were 25.0, 37.5 and 37.5 respectively [p<0.001]. Conclusions: Thyroid scintigraphy at this NBS centre over a 10 year period demonstrates dyshormonogenesis is by far the most frequent form of CHT and over 3 times more common than the historical frequency of 10%–15%. This is a paradigm shift in our understanding about the causes of CHT and has significant implications for genetic counselling and testing for families. Scintigraphy identifies and locates ectopia which might otherwise be incorrectly classified as dysplasia. Accurate CHT classification is crucial for initial levothyroxine dosage.